The Relationship Study of Teachers’ Perceptions Towards Professional Development and Their Job Satisfaction at Monastic Primary School in Namlan, Hsipaw, Northern Shan State, Myanmar - Nyunt, Nang Sein; Ye, Yan (Scholar: Human Sciences, 2019)
The main purpose of this study was to identify the relationship between teachers’ perceptions towards professional development and teachers’ job satisfaction at Monastic Primary School in Namlan, Hsipaw, Northern Shan State, Myanmar. A total of 60 full- time teachers from Monastic Primary School in Namlan Hsipaw, Northern Shan State, Myanmar during the academic year of 2017- 2018 were surveyed for this study. The research was designed as a quantitative and relationship study using the Guskey (2003) Professional development and Herzberg motivation-hygiene theory (1959) job satisfaction. The questionnaire used for this investigation consisted of two parts. There were 16 items pertaining to the three dimensions in part one which adopted from Meagher (2011), and 22 items with the six dimensions in part two which adopted from Mai (2013). The collected data were analyzed by using the mean, standard deviation and Pearson Product Moment Correlation Coefficient. Although the research findings showed that there were no significant relationship between teachers’ perceptions towards professional development and their job satisfaction, the responses of the teachers showed that professional development activities are beneficial and useful for their career.